Perceived Counselling Needs for Attainment of a Sustained Development Among Students’ in Abia State - Ikpekogu, Gertrude; Evans-Obinna, Rosemary. N (International Journal of Educational Management, 2021)
The study was carried out to explore perceived counselling needs among Business Studies students in Obingwa Local Government Area of Abia State for the attainment of a sustainable development in life during and after school. It adopted a descriptive survey design with a population consisting of 2169 of Business Studies teachers and 2148 JSII students in the study area and a sample size of 20 Business Studies teachers and 200 JSII students. A questionnaire titled: Teachers’ and Students’ Perceived Counselling Needs For A Sustained Development Questionnaire (TSPCNSD) made up of 4 sections, A,B,C and D respectively was used for data collection. The validity of the instrument was established by three experts in the departments of psychology and counselling, measurement and evaluation, and educational management. Cronbach’s Alpha statistics was used to establish the internal consistency with a reliability coefficient of 0.60. Data were analyzed using frequency, percentage, mean and standard deviation while the hypotheses were tested using t-test at 0.05 level of significance. Findings of the study revealed among others that the students requires different educational counselling, vocational, psychological and social needs to enable their attainment of a sustained development of self in the future. In conclusion, the findings revealed that there is no significant difference between the mean responses of the teachers and students on the three objectives of the study. The study recommended amongst others that government should ensure that these needs are integrated in to the instructions to earnable the attainment of a sustained development in the future. Keywords: Counselling, Sustainability, Development, Business Studies